Intraoperative transhepatic cholangiography - Estefan, Alberto; Pomi, Jorge; Bogliaccini, Gustavo; Pignata, Daniel; Beguiristain, Alberto; Praderi, Raúl (Cirugía del Uruguay, 1978)
Intra-operatory transhepatic cholangiography (whether by transhepatic puncture with needle; puncture or catherization of subcapsular duct; or direct approach of intrahepatic biliary duct) constitutes an alternative procedure in those cases when is no possibility of applying conventional methods. Fundaments, technique and selective criteria governing the different procedures are reviewed in this paper. Lack of cholangiographic visualization of biliary ducts of contralateral lobe and bil'iary junction. Makes simultaneous transhepatic cholangiography of said lobe imperative. Impossibility of puncturing an intrahepatic biliary duct does not signify that intrahepatic biliary dilation is absent. This condition can only be proved by the absence of dilated ducts upan direct approach. Out of the 27 cases in which intraoperatory transhepatic cholangiography was attempted, 25 (92,5 o) resulted in good quality hepatocholangiograms.